KORELASI ANTARA KESULITAN PSIKOSOSIAL DENGAN PENGALAMAN PERUNDUNGAN PADA SISWA SEKOLAH MENENGAH PERTAMA - Ni Ketut Putri Ariani; I Gusti Ayu Indah Ardani; Ni Ketut Sri Diniari; I Made Peri Ardiana Kusuma; Rifqi Fadly Arief (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Bullying among adolescents is a mental health problem that can have long-term effects on psychosocial development and individual well-being. Psychosocial difficulties are believed to contribute to increased vulnerability to bullying experiences among adolescents; however, empirical evidence in Indonesia remains limited. This study aims to analyze the relationship between psychosocial difficulties measured using the Strengths and Difficulties Questionnaire (SDQ) and bullying experiences measured using the Olweus Bullying Questionnaire among students of State Junior High School 5 Tembuku, Bangli Regency. This study employed an analytic cross-sectional design involving 46 ninth-grade students. Data were analyzed using correlation tests according to data distribution. The results showed a significant positive relationship between psychosocial difficulties and bullying experiences. The domains most strongly associated with bullying experiences included conduct problems, emotional problems, and peer problems. These findings indicate that higher levels of psychosocial difficulties are associated with a greater risk of experiencing bullying, particularly in behavioral and emotional aspects. The SDQ has potential as an early screening tool to identify at-risk students and to support the development of school-based mental health interventions integrated into bullying prevention efforts. ABSTRAK Perundungan pada remaja merupakan masalah kesehatan mental yang dapat berdampak jangka panjang terhadap perkembangan psikososial dan kesejahteraan individu. Kesulitan psikososial diduga berkontribusi terhadap meningkatnya kerentanan remaja terhadap pengalaman perundungan, namun bukti empiris di Indonesia masih terbatas. Penelitian ini bertujuan untuk menganalisis hubungan antara kesulitan psikososial yang diukur menggunakan Strengths and Difficulties Questionnaire (SDQ) dengan pengalaman perundungan yang diukur melalui Olweus Bullying Questionnaire pada siswa Sekolah Menengah Pertama Negeri 5 Tembuku, Kabupaten Bangli. Penelitian ini menggunakan desain potong lintang analitik dengan melibatkan 46 siswa kelas IX. Data dianalisis menggunakan uji korelasi sesuai distribusi data. Hasil penelitian menunjukkan adanya hubungan positif yang bermakna antara kesulitan psikososial dan pengalaman perundungan. Domain yang paling berkontribusi terhadap pengalaman perundungan meliputi masalah perilaku, masalah emosional, dan masalah teman sebaya.Temuan ini menunjukkan bahwa semakin tinggi kesulitan psikososial, semakin besar risiko remaja mengalami perundungan, terutama pada aspek perilaku dan emosional. SDQ berpotensi digunakan sebagai alat skrining dini untuk mengidentifikasi siswa berisiko, serta mendukung pengembangan intervensi kesehatan mental berbasis sekolah yang terintegrasi dalam upaya pencegahan perundungan.